Effect of different levels of environmental enrichment on the welfare of guppy (Poecilia reticulata) - Manenti, Isabella; Sicuro, Benedetto; Macchi, Elisabetta; Ponzio, Patrizia; Crosetto, Riccardo; Cavallari, Sharon; Tarantola, Martina; Mugnai, Cecilia (Frontiers in Fish Science, 2025)
IntroductionThe breeding of ornamental fish is increasingly widespread across the world. For this reason, assessing the welfare of ornamental fish in aquariums is becoming ever more important. This study wants to evaluate, through minimally invasive analyses, behavioral observations, and an analysis of cortisol concentrations in the water, how the absence or presence of environmental enrichment (EE) influences the welfare of guppies (Poecilia reticulata).MethodsIn total, 15 tanks, divided by EE level [without, with low (25%), and with high (75%) levels of EE], were considered. Fish were video-recorded and behavioral analyses were carried out. In addition, the cortisol concentrations in each tank's water were evaluated.ResultsIn the tanks with higher EE, behaviors such as wood, flotation, and plant feeding and courting, which are indicators of a good quality of life, were significantly more expressed. Bite behavior was also expressed more in high-level EE tanks, probably as a response to the territoriality of animals. The only stereotypy behavior, a stress index, was found to be significantly more expressed in tanks with low levels of EE. Finally, cortisol concentrations were found to be significantly higher in tanks with low levels of EE.DiscussionIn light of these results, we conclude that fish in tanks with higher EE levels showed better welfare statuses. Considering the use of EE in tanks is therefore useful for enabling these fish to express their species-specific behavioral repertoire and improve their quality of life.